Trapped in Your Own Net? Network Cohesion, Structural Holes, and the Adaptation of Social Capital - Gargiulo, Martin; Benassi, Mario (Organization Science, 2000)
This paper explores the tension between two opposite views on how networks create social capital. Network closure (Coleman 1988) stresses the role of cohesive ties in fostering a normative environment that facilitates cooperation. Structural hole theory (Burt 1992) sees cohesive ties as a source of rigidity that hinders the coordination of complex organizational tasks. The two theories lead to opposite predictions on how the structure of an actor's network may affect his ability to adapt that network to a significant change in task environment. Using data from a newly created special unit within the Italian subsidiary of a multinational computer manufacturer, we show that managers with cohesive communication networks were less likely to adapt these networks to the change in coordination requirements prompted by their new assignments, which in turn jeopardized their role as facilitators of horizontal cooperation within a newly created business unit structure. We conclude with a discussion of the trade-off between the safety of cooperation within cohesive networks and the flexibility provided by networks rich in structural holes.